High Success Rate of Prehospital and En Route Cricothyroidotomy Performed in the Israel Defense Forces: 20 Years of Experience. Issue 6 (8th December 2021) - Beit Ner, Eran; Tsur, Avishai M.; Nadler, Roy; Glassberg, Elon; Benov, Avi; Chen, Jacob
Abstract: Introduction: Securing the airway is a crucial stage of trauma care. Cricothyroidotomy (CRIC) is often addressed as a salvage procedure in complicated cases or following a failed endotracheal intubation (ETI). Nevertheless, it is a very important skill in prehospital settings, such as on the battlefield. Hypothesis/Problem: This study aimed to review the Israel Defense Forces (IDF) experience with CRIC over the past two decades. Methods: The IDF Trauma Registry (IDF-TR) holds data on all trauma casualties (civilian and military) cared for by military medical teams since 1997. Data of all casualties treated by IDF from 1998 through 2018 were extracted and analyzed to identify all patients who underwent CRIC procedures. Variables describing the incident scenario, patient's characteristics, injury pattern, treatment, and outcome were extracted. The success rate of the procedure was described, and selected variables were further analyzed and compared using the Fisher's-exact test to identify their effect on the success and failure rates. Odds Ratio (OR) was further calculated for the effect of different body part involvement on success and for the mortality after failed ETI. Results: One hundred fifty-three casualties on which a CRIC attempt was made were identified from the IDF-TR records. The overall success rate of CRIC was reported at 88%. In patients who underwent one or two attempts, the success rate was 86%. No difference was found across providers (physician versus paramedic). The CRIC success rates for casualties with and without head trauma were 80% and 92%, respectively (P = .06). Overall mortality was 33%. Conclusions: This study shows that CRIC is of merit in airway management as it has shown to have consistently high success rates throughout different levels of training, injuries, and previous attempts with ETI. Care providers should be encouraged to retain and develop this skill as part of their tool box.